1990
DOI: 10.1016/0248-4900(90)90328-z
|View full text |Cite
|
Sign up to set email alerts
|

Sperm penetration into immature mouse oocytes and nuclear changes during maturation: an EM study

Abstract: The ultrastructure of oocyte and sperm nuclei was studied in mouse ovarian oocytes inseminated in vitro and cultured for 1 1/2 and 3 h in a medium containing dbcAMP or lacking the maturation inhibitor. In oocytes blocked at the germinal vesicle (GV) stage, certain maturation-linked changes were noted. Sperm apposition and sperm-oocyte fusion were similar to that during fertilization of ovulated oocytes. The sperm nucleus and its nuclear envelope remained intact after penetrating into the ovarian oocyte. One an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 46 publications
1
35
0
Order By: Relevance
“…Szollosi et al (1990) have reported that although the sperm centriole is introduced into mouse oocytes at fertilization, it is not capable of behaving-as a centrosome and organizing microtubules, as was shown in the case of the human. Further differences in the expression of the embryonic genome, which occurs at the two-cell stage in the mouse (Dvorak et al, 1985) and between the four to eight-cell stage in the human (Sathananthan, 1992;Tesarik et al, 1988) may well necessitate the identification of an alternative mammalian model for both examining basic mechanisms and developing innovative techniques leading to successful ART.…”
Section: Resultsmentioning
confidence: 89%
“…Szollosi et al (1990) have reported that although the sperm centriole is introduced into mouse oocytes at fertilization, it is not capable of behaving-as a centrosome and organizing microtubules, as was shown in the case of the human. Further differences in the expression of the embryonic genome, which occurs at the two-cell stage in the mouse (Dvorak et al, 1985) and between the four to eight-cell stage in the human (Sathananthan, 1992;Tesarik et al, 1988) may well necessitate the identification of an alternative mammalian model for both examining basic mechanisms and developing innovative techniques leading to successful ART.…”
Section: Resultsmentioning
confidence: 89%
“…In rodent oocytes and early embryos, the presence of conspicuous intranuclear particles or granules has previously been reported (Palombi and Viron, 1977;Fakan and Odartchenko, 1980;Szollosi et al, 1990). In early embryos, it was concluded that the appearance of some of these particles was related to the progress of the nuclear changes during fertilization (Szollosi et al, 1990;Takeuchi and Takeuchi, 1989).…”
Section: Discussionmentioning
confidence: 87%
“…In early embryos, it was concluded that the appearance of some of these particles was related to the progress of the nuclear changes during fertilization (Szollosi et al, 1990;Takeuchi and Takeuchi, 1989). Certain categories of such granules were found to be similar to interchromatin or perichromatin granules, both of which are extranucleolar particles rich in ribonucleoproteins (Fakan, 1986), but a special category of larger granules (300-500 A in diameter) has also been identified in groups in the nucleoplasm of early mouse embryos, sometimes in the immediate vicinity of nucleoli (Fakan and Odartchenko, 1980).…”
Section: Discussionmentioning
confidence: 97%
“…However, the decondensastion of sperm chromatin does not necessarily indicate that this chromatin can undergo transformation into male pronucleus. In collaboration with Dan and Maryna Szollosi, we have demonstrated that the breakdown of the spermatozoon's nuclear envelope is a prerequisite for the transformation of the sperm nucleus into functional pronucleus (Borsuk and Tarkowski, 1989;Maleszewski 1990, 1992, Szollosi et al, 1990, Borsuk, 1991. However, Szollosi et al (1994) showed that the decondensation of sperm chromatin is not fully preventable by the lack of sperm nuclear envelope breakdown.…”
mentioning
confidence: 99%